Pregunta
upstudy study bank question image url

Determine the general solution of \( \cos x-\sin x=\sqrt{2} \)

Ask by Goodwin Hamilton. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The general solution is \( x = \frac{7\pi}{4} + 2k\pi \), where \( k \) is any integer.

Solución

Solve the equation \( \cos(x)-\sin(x)=\sqrt{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\cos\left(x\right)-\sin\left(x\right)=\sqrt{2}\) - step1: Move the expression to the right side: \(-\sin\left(x\right)=\sqrt{2}-\cos\left(x\right)\) - step2: Move the expression to the left side: \(-\sin\left(x\right)-\sqrt{2}=-\cos\left(x\right)\) - step3: Raise both sides to the \(2\)-th power\(:\) \(\left(-\sin\left(x\right)-\sqrt{2}\right)^{2}=\left(-\cos\left(x\right)\right)^{2}\) - step4: Calculate: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2=\cos^{2}\left(x\right)\) - step5: Rewrite the expression: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2=1-\sin^{2}\left(x\right)\) - step6: Move the expression to the left side: \(\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+2-\left(1-\sin^{2}\left(x\right)\right)=0\) - step7: Calculate: \(2\sin^{2}\left(x\right)+2\sqrt{2}\times \sin\left(x\right)+1=0\) - step8: Solve using the quadratic formula: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{\left(2\sqrt{2}\right)^{2}-4\times 2}}{2\times 2}\) - step9: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{\left(2\sqrt{2}\right)^{2}-4\times 2}}{4}\) - step10: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm \sqrt{0}}{4}\) - step11: Simplify the expression: \(\sin\left(x\right)=\frac{-2\sqrt{2}\pm 0}{4}\) - step12: Separate into possible cases: \(\begin{align}&\sin\left(x\right)=\frac{-2\sqrt{2}+0}{4}\\&\sin\left(x\right)=\frac{-2\sqrt{2}-0}{4}\end{align}\) - step13: Simplify the expression: \(\begin{align}&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\\&\sin\left(x\right)=\frac{-2\sqrt{2}-0}{4}\end{align}\) - step14: Simplify the expression: \(\begin{align}&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\\&\sin\left(x\right)=-\frac{\sqrt{2}}{2}\end{align}\) - step15: Evaluate the logic: \(\sin\left(x\right)=-\frac{\sqrt{2}}{2}\) - step16: Use the inverse trigonometric function: \(x=\arcsin\left(-\frac{\sqrt{2}}{2}\right)\) - step17: Calculate: \(\begin{align}&x=\frac{7\pi }{4}\\&x=\frac{5\pi }{4}\end{align}\) - step18: Add the period: \(\begin{align}&x=\frac{7\pi }{4}+2k\pi ,k \in \mathbb{Z}\\&x=\frac{5\pi }{4}+2k\pi ,k \in \mathbb{Z}\end{align}\) - step19: Rewrite the expression: \(x=\left\{ \begin{array}{l}\frac{5\pi }{4}+2k\pi \\\frac{7\pi }{4}+2k\pi \end{array}\right.,k \in \mathbb{Z}\) - step20: Check the solution: \(x=\frac{7\pi }{4}+2k\pi ,k \in \mathbb{Z}\) The general solution of the equation \( \cos x - \sin x = \sqrt{2} \) is \( x = \frac{7\pi}{4} + 2k\pi \), where \( k \) is an integer.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \( \cos x - \sin x = \sqrt{2} \), we can first rearrange it as: \[ \cos x = \sin x + \sqrt{2} \] Next, we can utilize the identity for the sine and cosine function to write: \[ \cos x - \sin x = \sqrt{2} \implies \frac{\sqrt{2}}{2} \cos x - \frac{\sqrt{2}}{2} \sin x = 1 \] This can be rewritten as: \[ \sqrt{2} \left( \frac{1}{\sqrt{2}} \cos x - \frac{1}{\sqrt{2}} \sin x \right) = 1 \] Recognizing \( \frac{1}{\sqrt{2}} \) as \( \cos\left(\frac{\pi}{4}\right) \) and \( \sin\left(\frac{\pi}{4}\right) \), we can express this in a unified way: \[ \sqrt{2} \left( \cos\left(x + \frac{\pi}{4}\right) \right) = 1 \] Dividing both sides by \( \sqrt{2} \), we get: \[ \cos\left(x + \frac{\pi}{4}\right) = \frac{1}{\sqrt{2}} = \cos\left(\frac{\pi}{4}\right) \] This leads us to the general solutions: \[ x + \frac{\pi}{4} = 2n\pi \pm \frac{\pi}{4} \quad (n \in \mathbb{Z}) \] This simplifies to: 1. \( x = 2n\pi \) (for the plus sign) \( - \frac{\pi}{2} \) 2. \( x = 2n\pi - \frac{\pi}{2} - \frac{\pi}{4} \) \( = 2n\pi - \frac{3\pi}{4} \) So the general solutions are: \[ x = 2n\pi - \frac{\pi}{2} \quad \text{and} \quad x = 2n\pi - \frac{3\pi}{4}, \, n \in \mathbb{Z} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad